Central ethical considerations for masters and doctoral research in business and management studies - Dan Remenyi (South African Journal of Business Management, 1998)
The subject of ethics is important in university research for a number of reasons. All masters or doctorate candidates need to be familiar with the Issues involved in order to avoid any problems or criticisms of their work. This article addresses a wide range of Issues including what should be researched, how the research should be conducted, how evidence should be collected and processed and how the finding should be treated. Issues related to plagiarism, thief of ideas, measuring instruments and choice of samples are also discussed. Finally the question of how much work may actually be done by others is also addressed.
Keywords: 650